Dirty Money : Does the Risk of Infectious Disease Lower Demand for Cash? - Cevik, Serhan (Washington, D.C. : International Monetary Fund, 2020)
The coronavirus pandemic is a global crisis like no other in modern times, and there is a growing apprehension about handling potentially contaminated cash. This paper is the first empirical attempt in the literature to investigate whether the risk of infectious diseases affects demand for physical cash. Since the intensity of cash use may influence the spread of infectious diseases, this paper utilizes two-stage least squares (2SLS) methodology with instrumental variable (IV) to address omitted variable bias and account for potential endogeneity. The analysis indicates that the spread of infectious diseases lowers demand for physical cash, after controlling for macroeconomic, financial, and technological factors. While the transactional constraints imposed by the COVID-19 pandemic could become a catalyst for the use of digital technologies around the world, electronic payment methods may not be universally available in every country owing to financial and technological bottlenecks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet